The Effect of Innovative Product, Brand Image, and Opinion Leader on Customer Retention in the Covid-19 Pandemic Era - Kurniawan, Gogi; D. Atinaja, Mariane (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2024)
The Covid-19 pandemic has been going on for two years, during which time there were many regulations in various fields, such as restrictions on community activities in various sectors which had an impact on changes in consumer behavior. These conditions encourage each company to survive, in the midst of uncertain conditions and increasingly fierce competition through a customer retention strategy built from innovation efforts, brand image enhancement, and opinion leaders as community marketing targets. For this reason, this study, which took 294 customers of Garudafood products by purposive sampling, aims to describe and examine the influence of innovative products, brand image, and opinion leaders on customer retention. Through path analysis it is known that innovative products have an effect on customer retention, and brand image affects customer retention; while the influence of the opinion leader on customer retention has a probability that cannot explain the influence or correlation to customer retention. The correlation value of determination explains that innovative products and brand images are able to make an effective contribution that is quite sufficient for the company's efforts to retain customers. Keywords: Innovative Product, Brand image, Opinion leader, Customer retention